Oral Mucosa and Nails in Genodermatoses: A Diagnostic Challenge - Tiziana Cantile (MDPI AG, 2021)
Genodermatoses represent a group of uncommon, hereditary, single-gene skin disorders, characterized by multisystem involvement, heterogeneous clinical manifestations and different degrees of morbidity and mortality. Some genodermatoses may have oral mucosa and nail involvement, since the oral cavity and cutaneous organ system, including nails, share a close embryologic origin. Nail disorders can manifest with nail hypoplasia or nail hypertrophy. Clinical pictures of affected oral mucosa can be extremely heterogeneous, ranging from asymptomatic papules to painful blisters, leukokeratosis, oral papillomas and fibromas to oral potentially malignant disorders and cancerous lesions. Oral mucosa and nails pathological features may occur synchronously or not and are usually associated with other systemic and skin manifestations. In some cases, oral mucosa and nails diseases may be distinct and constitute the principal sign of the genetic disorder, in other cases they represent only a part of the puzzle for the confirmation of the diagnosis. Continued awareness of the correlation between oral mucosa and nails findings can help physicians to diagnose genodermatosis in a timely manner, allowing more effective clinical management and prevention and/or early detection of complications. This article provides an overview of all specific genodermatoses affecting both oral mucosa and nails. Moreover, the correlation between teeth and nails is summarized in tabular form.